Estudo dos contaminantes do minério de ferro da Serra do Sapo, Conceição do Mato Dentro- MG - Fernando Prudencio Morais (2018)
This work aims to identify the forms and the main contaminating minerals responsible for the high levels of AL and P that occur in association with the itabirites of Serra do Sapo. This deposit is located in the Serra do Espinhaço region, in Conceição do Mato Dentro in Minas Gerais- Brazil. It is extending approximately 12 km in the NS direction, being the physical continuity of the important Serra da Serpentine Banded Iron formations (FFB). The geology of the deposit is former by a set of metasedimentary rocks belonging to the stratigraphic units of Serra da Serpentina Group, composed of sandstones, phyllites, shales, iron formations, carbonates and volcanic rocks. The itabirites are describe as part of the Serra do Sapo Formation, superior unit of the sequence, superposed to the schists and phyllites of the Meloso Formation. Iron formations with a high content of aluminum and phosphorus occur in contact with the schists of the basal unit and quatzites of the Serra do Sapo Formation. These contacts are tectonics and gradational generate a banded rock, with millimeter to centimetric levels containing high concentration of iron oxide, mainly hematite. This lithology has a silky texture and always occurs decomposed, friable, being describe as hematite-quartz-mica schists or classified as Itabirite with high content of contaminants - IFX. The classification of itabirites is according to the degree of weathering of the rock. Banded iron formations classified as fresh rock (IT) that also present high levels of phosphorus as contaminants and is classify as ITX - Itabirite with high phosphorus grade. Petrographic studies identified muscovite, chlorite and gibbsite as the main sources of aluminum for IFX samples. The high Al2O3 and P2O5 grades of these lithotypes are also explained by the supergenic formation process, where the space of the leached minerals is filled by chlorite and gibbsite. For ITX the high levels of phosphorus are related to apatite minerals that occur more frequently in this lithotype. The presence of tourmaline minerals, aligned and inbred between the microfractures of the quartz grains suggest a hydrothermal origin for these mineral formations in the itabirites. Geochemical data shows that IFX samples when normalized to PAAS are enriched in LREE compared to the other itabirites. These samples are also enriched in moving elements such as Ba and Sr. This indicated that the enrichment is due to the mobility of the LREE in an environment weathered without heavy REE. The studies done in the MLA indicated for the ITX a lower amount of hematite (33.8%) and a great quantity of quartz grains (64.24%). For all the granulometric intervals of this lithotype, the quartz was the main gangue mineral. Apatite and goethite, although occurring in a small proportion, are the main minerals bearing phosphorus. For the IFX the main gangue minerals are quartz (22.25%) and muscovite (14.23%) and chlorite with most clinochlore (Mg, Fe2+)5Al(Si3Al) O10(OH)8, in larger concentrations, together with muscovite and gibbsite appear as the main Al minerals.